38 Comparison study between the use of the amplatzer ductal occluder (ado) ii device and standard coil in the trans-catheter closure of persistent ductus arteriosus. (2nd February 2018) - Robinson, L; Rigby, ML; Slavik, Z; Fraisse, A
Abstract : Purpose: Transcatheter closure of patent ductus arteriosus (PDA) has become the preferred approach in clinical practice. The ADOII was developed for closure of small to moderate PDAs. Multiple studies have confirmed good early and long-term results but no studies comparing coil and the ADOII device have been reported. Methods: Retrospectively, we compared the residual shunt rate and complication rate between the ADOII device and the coil in all patients aged 0–18 years who underwent transcatheter closure of PDA between September 2014 and October 2016 at the Royal Brompton Hospital. Results: Immediate residual shunt (RS) rate was 13.9% (5/36 cases) for the Flipper coil and 13.3% (4/30 cases) for the ADOII device (p=0.948). Echocardiographic assessment within 24 hours demonstrated a reduction in shunt rate in the ADOII group to 10% (3/30 cases) compared to the coil cohort, still maintaining a shunt rate of 13.8% (5/36 cases) (p=0.63). At follow up, the RS rate was 4.2% (1/24) in the ADOII group compared to 0% for the coil group (p=0.444). Complications were higher with Flipper coils (4 cases/11.1%) compared to the ADOII device (2 cases/6.7%) (p=0.532). An additional device was required in 3 cases (8.3%) of PDAs corrected with Flipper coil, compared to only 1 case (3.3%) in the ADOII cohort (p=0.397). Conclusion: Transcatheter occlusion of small to moderate PDAs is safe and effective with both ADOII devices and coils. The ADOII device seems to be associated with fewer complications and reduced residual shunt rates initially but larger studies are required to better compare the two systems.